SOLDIERS OF THE EASTERN LEGIONS OF THE WEHRMACHT IN THE RANKS OF THE PARTISANS OF WESTERN BELARUS: TRANSITIONS, ACTIVITIES, FURTHER DESTINES (1941–1944) - I. V. CHARNIAUSKI (Кавказология, 2021)
During the war against the Soviet Union in 1941–1945, the German leadership turned to the idea of creating and using formations from the Caucasian and Turkic peoples living on the territory of the USSR to their advantage. They went down in history under the general name of the Eastern Legions. Details of their organization and combat use at the front are reflected in a number of works by researchers. The same cannot be said about the ties of the Eastern Legions with the Soviet partisans of Western Belarus. The purpose of the study is to identify cases of transitions from these units of the German army to the opposing side in this region and determine their total number. The article focuses on the motivation and contribution to the fight in the enemy rear of the former soldiers of the Eastern Legions, and also examines their fate after joining the Red Army units. The scientific novelty lies in considering the issue on the territory of a particular region with its own specifics.